Aktivitas Antioksidan Dan Uji Organoleptik Minuman Herbal Ekstrak Belimbing Wuluh Dengan Variasi Penambahan Ekstrak Kulit Buah Naga Dan Daun Stevia - Setyowati, Ratna Dewi; , Dra. Suparti M,Si (2016)
Starfruit also contains flavonoids, saponoin, tannins, glucosides, calcium, potassium, vitamin C and peroxidase. Dragon fruit skins contain anthocyanins manifold sianidin 3-glucoside ramnosil 5-glucoside. Anthocyanins may serve to degrade cholesterol in the blood. Stevia leaf is a leaf that is often used as a natural sweetener for foods and beverages. Phytochemical compounds contained in stevia leaves are alkaloids, saponins, tannins, phenolics, flavonoids, triterfenoid, steroids, glycosides. This study aims to determine the antioxidant activity and the organoleptic quality herbal extract syrup starfruit with variations addition of dragon fruit peel and leaves of stevia. The study design used completely randomized design (CRD), which consists of two factors, namely: Factor 1 is the dragon fruit skin extract ( 25 ml, 50 ml, 75 ml ) and the second factor is the concentration of stevia leaves ( 0.6 g; 0.9 g ) with repeated 3 times repetition. Based on the findings contained in the highest antioxidant activity of 80.83% N3S2 treatment (extract formulation starfruit 50 ml with dragon fruit skin extracts 75 ml and 0.9 g stevia leaf), while the antioxidant activity was lowest for the treatment N1S2 29.30 % (extract formulation starfruit 50 ml with dragon fruit skin extracts 25 ml and 0.6 g stevia leaf). Treatment quality herbal syrup N3S2 most dominant in the treatment preferred by the panelists while treatment quality herbal syrup is less well to treatment less favored N1S1 panelists